Bathymetry and morphometric analysis of Greek natural lakes through a hybrid GIS-acoustic methodology - T. Perivolioti; A. Apostolakis; D. Papadimos; V. Tsiaoussi (2025)
Inland Waters, 1–17. https://doi.org/10.1080/20442041.2024.2447173